The Effect of Inclusion Style And Reciprocal Style in Performing Jump Shot in Handball - Abed al minaam, Bilal; Mahmoud, Mohammed (Journal of Physical Education, 2020)
Teaching as a process still requires new strategies so as to include all students in the learning process. The researchers combined inclusion and reciprocal styles together in one teaching session to benefit from both styles, save time and effort and to identify their effect on learning handball jump shot. The researchers used the experimental method on sophomore college of physical education and sport sciences college. The teaching program consisted of (3) teaching session for three weeks. The results showed significant effects of using inclusion and reciprocal style yet the reciprocal style was better that command style followed by the teacher in learning jump shot in handball. Finally the researchers recommended using inclusion style for learning skills and specially team sport skills.